2018
DOI: 10.4067/s0717-95022018000100290
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación Postural y Prevalencia de Hipercifosis e Hiperlordosis en Estudiantes de Enseñanza Básica

Abstract: BRITO-HERNÁNDEZ, L.; ESPINOZA-NAVARRO, O.; DÍAZ, G. J. & LIZANA, P. A.Evaluación postural y prevalencia de hipercifosis e hiperlordosis en estudiantes de enseñanza básica. Int. J. Morphol., 36(1):290-296, 2018. RESUMEN:El alineamiento incorrecto de la columna vertebral origina estrés y una tensión innecesaria que afecta el aparato locomotor. El objetivo de este trabajo fue identificar y establecer la prevalencia de hipercifosis e hiperlordosis y su relación con el índice de masa corporal (IMC) e índice cintura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…The whole sample size of the included studies was 1,757,107 children and adolescents with ages ranging from 0 to 21 years old. All studies used BMI as OW/OB indicator, whereas three studies additionally reported fat mass composition [18][19][20] , two reported muscle mass composition 18,20 , two reported waist circumference 21,22 and one reported height-waist circumference 23 . BMI was always used to measure the obesity degree, and a wide range of cut-off points were identified: 22 studies used the Extended International (IOTF) cut-offs , seven the 90 th and 97 th percentiles (OW and OB respectively) [45][46][47][48][49][50][51] , seven cut-off points from their countries (Czech Republic, Mexico, Poland, Taiwan and USA) 18,[52][53][54][55][56][57] , six the World Health Organization cut-offs [58][59][60][61][62][63] , six the Centers for Disease Control and Prevention cut-offs [64][65][66][67][68][69] , one the National Institute of Health cut-offs 70 , and one did not report it 71 .…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The whole sample size of the included studies was 1,757,107 children and adolescents with ages ranging from 0 to 21 years old. All studies used BMI as OW/OB indicator, whereas three studies additionally reported fat mass composition [18][19][20] , two reported muscle mass composition 18,20 , two reported waist circumference 21,22 and one reported height-waist circumference 23 . BMI was always used to measure the obesity degree, and a wide range of cut-off points were identified: 22 studies used the Extended International (IOTF) cut-offs , seven the 90 th and 97 th percentiles (OW and OB respectively) [45][46][47][48][49][50][51] , seven cut-off points from their countries (Czech Republic, Mexico, Poland, Taiwan and USA) 18,[52][53][54][55][56][57] , six the World Health Organization cut-offs [58][59][60][61][62][63] , six the Centers for Disease Control and Prevention cut-offs [64][65][66][67][68][69] , one the National Institute of Health cut-offs 70 , and one did not report it 71 .…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…BMI was always used to measure the obesity degree, and a wide range of cut-off points were identified: 22 studies used the Extended International (IOTF) cut-offs , seven the 90 th and 97 th percentiles (OW and OB respectively) [45][46][47][48][49][50][51] , seven cut-off points from their countries (Czech Republic, Mexico, Poland, Taiwan and USA) 18,[52][53][54][55][56][57] , six the World Health Organization cut-offs [58][59][60][61][62][63] , six the Centers for Disease Control and Prevention cut-offs [64][65][66][67][68][69] , one the National Institute of Health cut-offs 70 , and one did not report it 71 . Regarding postural alterations, four articles studied forward head [72][73][74][75] , five rounded shoulder 18,19,72,73,76 , 12 thoracic hyperkyphosis 10,18,23,34,59,70,72,74,75,77-79 , 14 lumbar hyperlordosis 18,20,23,34,48,59,72,74,<...>…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…En la mayor parte de casos diagnosticados, la afección tiende a aparecer en la etapa de la niñez, sin ninguna causa en común, dicha condición es referida como una lordosis juvenil benigna; no obstante, se debe mencionar que su aparición puede darse en cualquier momento del ciclo evolutivo de un individuo, siendo los siguientes aspectos los posibles causantes: malos hábitos posturales; padecer de osteoporosis; presencia de cifosis; sufrir de discitis, que contempla un problema en los discos localizados entre las diferentes vertebras de la columna; ser obeso; la acondroplasia, problema de crecimiento que afecta a los cartílagos de los huesos largos y presentar espondilolistesis, que conlleva un escenario donde la vertebra se posiciona hacia adelante o atrás con relación a la siguiente (52).…”
Section: Ilustración 4 Lordosisunclassified